2019
DOI: 10.3390/pathogens9010023
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Potential of Selected Essential Oils on Fusarium spp. Growth and Mycotoxins Biosynthesis in Maize Seeds

Abstract: Owing to their rich chemical composition, essential oils (EOs) have many interesting properties, including antimicrobial activities. The presence of Fusarium and their secondary metabolites, mycotoxins, in cereal crops is a serious problem in agriculture, which consequently affects food quality. The aim of the present study was to investigate the effects of selected EOs on the growth of Fusarium graminearum and F. culmorum and the biosynthesis of mycotoxins in maize seeds. Chromatographic analysis of ergostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 74 publications
0
36
0
2
Order By: Relevance
“…The effects of twelve essential oils on F.oxysporum and compared with commercial fungicides was examined and found that fungicide Prosaro -250 EC and essential oils from clove, fennel, anise, true lavender, peppermint, thyme, basil , tea and sage exhibited the same inhibitory effect (Palfi et al ., 2019). The inhibition of F.graminearum and F. culmorum in maize and wheat seeds and reduction in the Deoxynivalenol, zearalenone and group B trichothecenes level with the application of essential oils was reported ( Perczak et al, 2019a ;2019b). Kumar et al (2016) reported the inhibition of growth and mycotoxin (ZEA) production by Fusarium graminearum at 3.5 and 3 mg/mL respectively by turmeric essential oil.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of twelve essential oils on F.oxysporum and compared with commercial fungicides was examined and found that fungicide Prosaro -250 EC and essential oils from clove, fennel, anise, true lavender, peppermint, thyme, basil , tea and sage exhibited the same inhibitory effect (Palfi et al ., 2019). The inhibition of F.graminearum and F. culmorum in maize and wheat seeds and reduction in the Deoxynivalenol, zearalenone and group B trichothecenes level with the application of essential oils was reported ( Perczak et al, 2019a ;2019b). Kumar et al (2016) reported the inhibition of growth and mycotoxin (ZEA) production by Fusarium graminearum at 3.5 and 3 mg/mL respectively by turmeric essential oil.…”
Section: Resultsmentioning
confidence: 99%
“…With the need to guarantee high-quality seeds, seed treatments with antimicrobials represent a crucial and important step for reduction of seed infections [ 16 ]. Integrated pest management strategies are designed to provide environmentally sound and economically feasible alternatives for seedborne disease management [ 17 ]. These strategies are needed to minimize the inoculum of potential pathogens on seeds, and they draw on management components that are currently available to farmers, or can be made available in the near future [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant essential oils are composed from mixture of monoterpenes, diterpenes, sesquiterpenes and their oxidatives derivatives such as alcohols, aldehydes, ketones, ethers, esters, phenols and oxides [17,18]. Essential oils are often used in cosmetics and pharmaceutical industry [19]. The alternative use of EOs as biological pesticides is an important element of modern organic farming [16].…”
Section: Introductionmentioning
confidence: 99%